Strategi Komunikasi Pembinaan Pembudidayaan Kambing Boer untuk Meningkatkan Taraf Ekonomi Masyarakat di Desa Wonosari, Kecamatan Wonosari, Kabupaten Malang, Provinsi Jawa Timur - Siti Azizah (FISIP Universitas Atma Jaya Yogyakarta, 2010)
Abstract : She research was conducted in Wonosari Village, Malang Regency from August to October 2009. The aims of the research are: (1) to establish a communication strategy for goat farmers according to their needs and wants, (2) to socialize the program to motivate the audience to breed Boer goat, and (3) to get potential skill and to give knowledge in Boer goat breeding activities. Research material was goat farmers who earn below Rp 146.837,00 per capita/month. Research methods were: observation and participation, interview and data triangulation. Sample was taken from key informants and goat farmer. Sampling technique was purposeful selection, selecting goat farmers to be research respondents. The research results then help researchers to establish a set of communication components strategie such as how to choose a communicator, what languages to use, the type of presentation, and the use of humor. Media/channels preferred are posters, slides, leaflets, booklets, magazines and seminar. To enhance the knowledge level, goat farmers were also taken to Sumbersekar Laboratory to give real experience to gain highest level of experience compared to audio atau audio visual media.